1992
DOI: 10.1128/iai.60.9.3528-3532.1992
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a conjugate vaccine composed of pneumococcus type 14 capsular polysaccharide bound to pertussis toxin

Abstract: Type 14 is one of the common types isolated from patients of all ages with infections caused by Streptococcus pneumoniae. Its capsular polysaccharide (Pnl4) is composed of a neutrally charged tetrasaccharide repeat unit.Pnl4 does not elicit protective levels of antibodies in infants and children and is a less than optimal immunogen of the 23-valent vaccine for adults. Pertussis toxin (PT) is both a virulence factor and protective antigen of Bordetella pertussis: it is not soluble at neutral pH and forms insolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 36 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…This IgG subclass imbalance with defective PS Ag response might be explained by a delayed development of B cell maturation, suggestive of transient hypogammaglobulinemia. Schneerson et al 27 have recently proposed the enhanced effect of a conjugate vaccine of pneumococcal PS bound to PT on the specific Ab response to PS. The combined vaccination of DPT and pneumovax might be advantageous for the patients with IgG subclass deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This IgG subclass imbalance with defective PS Ag response might be explained by a delayed development of B cell maturation, suggestive of transient hypogammaglobulinemia. Schneerson et al 27 have recently proposed the enhanced effect of a conjugate vaccine of pneumococcal PS bound to PT on the specific Ab response to PS. The combined vaccination of DPT and pneumovax might be advantageous for the patients with IgG subclass deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this observation, preliminary studies showed that the vaccine responses of the aged mice can be enhanced by supplementation with IL-10, a cytokine that can antagonize IFN-␥ production (29a, 34). Also, strategies to make the vaccine T-cell dependent may not be as important for older individuals (6,38,44), since the necessary T-cell-derived cytokine, IL-5, is already high in aged mice but is unable to help the vaccine response. In summary, these studies showed for the first time that the hyporesponsiveness of older animals to pneumococcal PS vaccine is due to an accessory cell deficiency and have suggested strategies to increase the vaccine efficacy for this population.…”
Section: Downloaded Frommentioning
confidence: 99%
“…CPS expression for naturally occurring phase variants of V. vulnificus, as well as for genetically defined mutants, was evaluated by ELISA, IEM, or FC analyses with a CPS-specific monoclonal antibody. Difficulties in obtaining monoclonal or polyclonal antibodies to purified capsule preparations have been reported (29), but increased antibody responses can be achieved by the use of protein carriers (6). Previously described tetanus toxoid conjugates to purified V. vulnificus CPS elicit the greatest polyclonal response in mice (10) and were used to produce monoclonal antibodies in mice.…”
Section: Discussionmentioning
confidence: 99%